A POTENTIAL ZOONOTIC PARASITE: CRYPTOSPORIDIUM PARVUM TRANSMISSION IN RATS, PIGS AND HUMANS IN WEST LOMBOK, INDONESIA. - Resnhaleksmana, Ersandhi; Wijayanti, Mahardika Agus; Artama, Wayan Tunas (African Journal of Infectious Diseases (AJID), 2021)
Background: Cryptosporidium is a neglected zoonotic disease, but with the expansion of human communities its incidence is increasing. Animals such as rats and pigs can act as intermediate hosts and transmit Cryptosporidium to humans due to their proximity. Transmission occurs due to the ability of Cryptosporidium to survive in a new host. The research aimed to identify and describe the transmission of Cryptosporidium from animals to humans. Materials and Methods: This research was a cross sectional study and samples were collected from 84 rats, 205 pigs, and 438 humans in West Lombok. Feces samples were examined using polymerase chain reaction (PCR) and sequencing to isolate the presence of Cryptosporidium, and identify the genetic similarity of the parasites found in rats and pigs with those that infect humans. Results: The PCR results found Cryptosporidium parvum in 4.76% (4/84) in rats; 6.34% (13/205) in pigs; and 0.91% (4/438) in humans. The sequencing results showed genetic kinship of C. parvum in rats, pigs, and humans. There are genetic similarities of Cryptosporidium isolates from West Lombok with C. suis isolates of cattle, from Uganda and C. suis isolates of pigs, from Slovakia. Conclusion: There are genetic similarities of Cryptosporidium in animals and humans, requiring that the Public Health programs in those contaminated areas must receive priority attention to prevent further transmission of these potentially fatal parasites.